Anti-inflammatory effects of three withanolides isolated from Physalis angulata L. in LPS-activated RAW 264.7 cells through blocking NF-κB signaling pathway. (10th August 2021) - Wang, Luqiong; Lu, Shiqing; Wang, Liying; Xin, Min; Xu, Yaoyao; Wang, Ge; Chen, Daquan; Chen, Lixia; Liu, Sheng; Zhao, Feng
Abstract: Ethnopharmacological relevance: Physalis angulata L. is commonly used in many countries as popular medicine for the treatment of a variety of diseases such as malaria, hepatitis, dermatitis and rheumatism. But the anti-inflammatory active constituents of this medicinal plant and their molecular mechanism are still not elucidated clearly. Aim of the study: The aim of the study is to isolate and identify a series of compounds from the ethanolic extract of Physalis angulata L., and to investigate the anti-inflammatory activities in vitro and the molecular mechanism of physagulin A, physagulin C, and physagulin H. Materials and methods: In order to further understand the anti-inflammatory mechanism of the three compounds, their potential anti-inflammatory activities were investigated in vitro in LPS-activated RAW 264.7 macrophage cells by Griess assay, ELISA, Western blot and immunofluorescence methods in the present study. Results: Physagulin A, physagulin C, and physagulin H could not only inhibit the release of NO, PGE2, IL-6 and TNF-α, but also could down-regulate the expression of iNOS and COX-2 proteins. Furthermore, physagulin A, physagulin C, and physagulin H could remarkably block the degradation of IκB-α and the nuclear translocation of NF-κB/p65 in LPS-activated RAW 264.7 cells. However, none of them could inhibit the phosphorylation of MAPKs family proteins ERK, JNK and p38. Thus, the anti-inflammatory actions of physagulin A, physagulin C, and physagulin H were mainly due to the significant inhibition of NF-κB signaling pathway rather than MAPKs signaling pathway. Conclusions: All the results clearly showed that physagulin A, physagulin C, and physagulin H demonstrated potent anti-inflammatory activity and can be used as novel NF-κB inhibitors. They are potential to be developed as an alternative or complementary agents for inflammatory diseases. Graphical abstract: Image 1 Highlights: Physagulin A, physagulin C, and physagulin H inhibited the overproduction of NO, PGE2, TNF-α and IL-6 induced by LPS. They down-regulated the expression of iNOS and COX-2 proteins. Physagulin A, physagulin C, and physagulin H exert anti-inflammatory effects by blocking the NF-κB pathway.